LANDASAN PERSEPSI MASYARAKAT TERHADAP KIAI YANG BERPOLITIK PRAKTIS - Mohammad Adi; Ridan Muhtadi (LP2M IAI Miftahul Ulum Pamekasan, 2017)
The development of practical politics in Indonesia leads some Kyai to involve in politics. These are utilized by parties in local and national level, especially in the matter of vote getter. That is why, Kyai is faced with a world of politics that full of interest and uncertainty. The research was carried out after the contestation of the general elections in 2014. Research location is conducted in Socah Village, Socah, Bangkalan. The purpose of this study is to describe the perception of society on Kyai who involves in politics and to determine the description of Kyai’s condition who involves in politics in Socah Village, Socah, Bangkalan. The study uses perception theory. The method of study is descriptive qualitative by applying case study approach. The researcher obtains data by using deep interview and observation to informants based on the criteria (purposif). The data collected then is analyzed by using qualitative analysis technique. Next, the data is examined for the validity by using source triangulation in order to obtain the valid data. The result of study is described through information exposure obtained during the research. The result shows that there are different views of Socah people about Kyai who involves in politics and some of them judge it as perfectly natural. Nevertheless, the participating of Kyai in practical politics results in more negative values (madharat) than the positive one (maslahat). People of socah still hold their ancestor tradition in which they are commanded to obey any Kyai’s commands, including in political choice. That is why, the majority of Socah society allow Kyai to participate in politics. It is based on an assumption of some Socah people that Kyai is more appropriate to lead the bureaucracy because he has a wide view and also a role model in doing a daily activity.